INTERACTION BETWEEN BISCHOFIA JAVANICA BLUME (EUPHORBIALES: EUPHORBIACEAE) AND COLOANA CINEREA DWORAKOWSKA (HOMOPTERA: CICADELLIDAE): A PROTECTIVE ENZYME PERSPECTIVE - Zhen-De Yang; Yan-Juan Sun; Shu-Zhong Yu; Xia-Lin Zheng (Journal of Animal and Plant Sciences, 2015)
Coloanacinerea Dworakowska (Homoptera: Cicadellidae) is a phloem-feeding pest on BischofiajavanicaBlume (Euphorbiales: Euphorbiaceae), which is the main species of avenue tree in the urban landscape of China. Understanding their relationship is conducive to exploring the coevolution of both of them and the effective management of insect pests. In this study, their interaction was studied from a protective enzyme perspective. Results showed that Catalase (CAT), peroxidase (POD) and superoxide dismutase (SOD) activities in B. javanica leaves were evidently enhanced by population density, feeding duration and their interaction of C. cinerea. CAT, POD, SOD, glutathione S-transferase (GST) and amylase (AMY) in C. cinerea were conversely affected by foliage maturity of B. javanica, feeding duration and their interaction. These changes in physiological compositions of both C. cinerea and B. javanica following stress or damage suggest that they have coevolved to an adaptation against each other.
Keywords: Landscape plant; Insect pest; Protective enzyme; Coevolution